2019
DOI: 10.1038/s41598-019-56416-9
|View full text |Cite
|
Sign up to set email alerts
|

RORγt+ Treg to Th17 ratios correlate with susceptibility to Giardia infection

Abstract: Infections with Giardia are among the most common causes of food and water-borne diarrheal disease worldwide. Here, we investigated Th17, Treg and IgA responses, and alterations in gut microbiota in two mouse lines with varying susceptibility to Giardia muris infection. Infected BALB/c mice shed significantly more cysts compared with C57BL/6 mice. Impaired control of infection in BALB/c mice was associated with lower Th17 activity and lower IgA levels compared with C57BL/6 mice. The limited metabolic activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 64 publications
(92 reference statements)
2
15
0
Order By: Relevance
“…BALB/c mice infected with Giardia muris showed a more significant Treg response than C57BL/6 mice and shed more Giardia cysts. Interestingly, BALB/c mice showed larger populations of Clostridia than the C57BL/6 mice, further suggesting that presence of certain commensal species may drive specific immune responses ( Yordanova et al, 2019 ). However, in contrast to previous studies, although BALB/c mice showed increased SFB populations, they showed reduced Th17 responses ( Yordanova et al, 2019 ).…”
Section: Role Of the Microbiome In Giardia Pathogementioning
confidence: 99%
See 1 more Smart Citation
“…BALB/c mice infected with Giardia muris showed a more significant Treg response than C57BL/6 mice and shed more Giardia cysts. Interestingly, BALB/c mice showed larger populations of Clostridia than the C57BL/6 mice, further suggesting that presence of certain commensal species may drive specific immune responses ( Yordanova et al, 2019 ). However, in contrast to previous studies, although BALB/c mice showed increased SFB populations, they showed reduced Th17 responses ( Yordanova et al, 2019 ).…”
Section: Role Of the Microbiome In Giardia Pathogementioning
confidence: 99%
“…ATB = antibiotic treatment; * = phylum; + = class; $ = family # = genus; 1 = patients with severe malabsorption; 2 = taxa both enriched and decreased in separate studies. Microbiota dysbiosis in response to Giardia muris infections (i.e., Yordanova et al, 2019 ) is not represented in this figure.…”
Section: Alterations To the Microbiota During Giardia mentioning
confidence: 99%
“…10-to 12-week old mice were infected and sacrificed at the indicated time points as previously described. 8 All animal experiments were performed in accordance with the National Animal Protection Guidelines and approved by the Berlin Ethics Committee for the Protection of Animals (G0113/15).…”
Section: Mice and G Muris Infectionmentioning
confidence: 99%
“…Surface and intracellular stainings were performed as previously described, 8 applying the antibodies listed in Table S1. Samples were analysed on a Canto II flow cytometer (BD Biosciences), and data were analysed using FlowJo software Version 10 (Tree star Inc.).…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
See 1 more Smart Citation